The Role of Sensor Technology in the Development of Environmental Monitoring Systems: A Systematic Review of the Literature - Dian Ramadhani (Penelitian dan Pengembangan Ilmu, 2024)
The development of an environmental monitoring system plays an important role in efforts to maintain environmental sustainability. Sensor technology has become a significant solution in improving the accuracy and effectiveness of environmental monitoring. In this literature review, we evaluate the role of sensor technology in the development of environmental monitoring systems through a comprehensive analysis of relevant literature. We highlight recent developments in sensor technology, its applications in environmental monitoring, and future challenges and opportunities. The results show that sensor technology has made a significant contribution to improving environmental monitoring capabilities, although there are still several challenges that need to be overcome. The implications of these findings for practice and research in the field of environmental monitoring are also discussed in depth.